Kualitas Informasi Katalog Digital Akun Instagram @SantflowersBouquet dalam Keputusan Pembelian Produk Santflowers - Faradita Putri; Hudi Santoso (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The rapid development of social media, particularly Instagram, has transformed consumers’ information-seeking behavior and purchasing decision processes, making information quality in digital catalogs a crucial factor in visual-based marketing. However, studies examining information quality in Instagram-based digital catalogs for highly customized products remain limited. This study aims to analyze the relationship between the quality of digital catalog information and purchasing decisions on the @santflowersbouquet account. A quantitative approach with a survey method was employed, involving 95 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity, reliability, and Spearman’s Rank correlation tests. The results indicate that information quality is categorized as high, with accuracy (92.6%) and timeliness (86.3%) as the dominant indicators. Purchasing decisions are also in the high category, with the time of purchase indicator reaching 96.8%. The correlation test shows a positive and significant relationship with a coefficient of 0.621 (p<0.001), indicating a strong association. These findings suggest that improving the quality of digital catalog information significantly contributes to enhancing purchasing decisions. Therefore, businesses are encouraged to optimize information quality as part of their digital marketing communication strategy.